2021
DOI: 10.17159/2413-3221/2021/v49n2a12785
|View full text |Cite
|
Sign up to set email alerts
|

Influence of public agricultural extension on technology adoption by small-scale farmers in Zimbabwe

Abstract: This paper presents the findings of challenges facing Zimbabwe’s extension services and how these have affected the adoption of technologies they render to small-scale farmers. This study uses a critical review of relevant literature on Zimbabwe’s primary public extension agency (AGRITEX). Additionally, 21 key informant interviews (KIIs) were conducted to corroborate data collected in secondary research on extension approaches currently in use, the key factors affecting technology adoption, and the technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…Lack of access to agricultural information, particularly farm management information, is a common characteristic of small-scale farmers [22,23]. In Zimbabwe, they are particularly reliant on extension workers, other farmers through their farmers' clubs and, to a small extent, radio [18,22,23].…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Lack of access to agricultural information, particularly farm management information, is a common characteristic of small-scale farmers [22,23]. In Zimbabwe, they are particularly reliant on extension workers, other farmers through their farmers' clubs and, to a small extent, radio [18,22,23].…”
Section: Tablementioning
confidence: 99%
“…Most small-scale farmers depend on their own indigenous knowledge generated through many years of farming experience in their own communities to guide crop Evaluation of the Role of Small-Scale Farmers in Soil and Water Conservation Management… DOI: http://dx.doi.org/10.5772/intechopen.108889 management decisions [18,22,23,25] (Table 2). Although reliable, indigenous knowledge keeps farmers operating at low levels of productivity [11].…”
Section: Use Of Indigenous Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…At the micro level, the financial challenges faced by the state universities have adversely affected their investment in facilities, equipment and training materials. The lack of proper investment in agricultural research and education and the remuneration of staff has in turn affected the retention of highly skilled scientists (Masere & Worth, 2021). One female AEO noted that when resources are scarce, male AEOs are prioritised in the allocation of motorbikes.…”
Section: Financial and Economic Barriers To Curriculum Reformmentioning
confidence: 99%
“…Curricula have been slow to respond to new trends such as precision agriculture, to the adoption of remote sensing and also to the use of geographic information systems (GIS) (Lele & Goswami, 2017). In fact, the adoption of technology has become a key enabler in the dissemination of agricultural knowledge and practices by farmers and extension officers (Ismoilov, 2021;Masere & Worth, 2021); this means that their inclusion in Agriculture degree and diploma programmes has become essential. Besides, recent studies have revealed that technology is an important tool with which to encourage engagement among the current generation of students, including motivating learners to enrol in programmes and to encourage student retention (Bond & Bedenlier, 2019).…”
Section: Technological Barriersmentioning
confidence: 99%